Inter-rater Agreement for Diagnoses of Epilepsy in Pregnant Women - Khoshbin, Shahram (2013)
We report on inter-rater agreement in assessing the types of seizures exhibited by one hundred mothers ascertained in a study of the teratogenicity of maternal epilepsy and antiepileptic drugs. A summary of each woman’s medical record, and a one-page report of her responses to questions about her epilepsy, were reviewed independently by six neurologists, three in pediatric neurology and three in adult neurology. Agreement was measured by the kappa statistic and log-linear modeling techniques. The adult neurologists agreed with each other 59 percent of the time, with agreement higher when all three used information from the patients’ records, such as an EEG, rather than when depending on the woman’s responses to questions about her epilepsy. Pediatric neurologists agreed with each other 44% of the time and tended to rely more heavily, than adult neurologists, on information in the patients’ records, such as an EEG or a prior diagnosis.